Report on the Census of Government Employees (As on 31-3-84) Union Territory of Goa, Daman and Diu - Planning Commission (Planning Commission, 1984)
The Report on the Census of Government Employees is regular publication of the Directorate of Planning, Statistics end Evaluation. The present issue, thirteenth in the series, gives the Census results for the year 1984; reference period of the survey being the 31st March 1984. It contains information on employment end its pattern of distribution in various Government offices of the Union Territory Administration, Central Govt, offices and Semi—Govt Organizations located in this Territory and Local Bodies. I record my gratitude for the help extended by various Government and Semi-Government Departments in making – available, the required information. My thanks are also duo to Shri S.M. Naik, Statistical Officer, who supervised the collection and compilation of data and prepared the preliminary draft of the report. He was assisted by Shri F.O. Colace, Research Assistant and Shri C.B. Cota, Investigator. Shri G. V. Kamat, Joint Director made valuable suggestions at various at stages .My thanks are due to him also. Suggestions for improvement of the publication are always welcome.
Government of Goa, Daman and Diu, Panaji
Directorate of Planning Statistics and Evaluation
Keywords: Employees of Govt. of Goa; Daman & Diu; Employees; of the Central Govt Offices; Employees of Semi-Government Organizations and other State Governments; District wise number of regular employees; Group-wise number of Employees; Scope and Coverage; Concepts and Definitions; Directorate of Planning; Statistics and Evaluation; non-regular employees working; Department wise Employment.